Electronic Banking Payment and Settlement System: Adoption Trend Among Customers - Garga, Paw an Kumar; Sharma, Vikas (Gyan Management Journal, 2008)
The modernisation of payment and settlement system is the backbone of any nation because it helps in economic development, fast mobilisation of funds and capital formation. Majority of banks have been modernising their existing payment and settlement system as a strategic tool for fast settlement of funds across the nation. The current paper discusses the deployment of modern payment and settlement system by the banks in Himachal Pradesh and their adoption among the customers in their day to day life. This analysis is essential because banks have invested huge money in modernising traditional face of banking and providing 24X7 hrs service to customers. This will act as a major feedback not only to the banks but also to the Government to reframe their policies.
Keywords: Electronic Banking; Payment and Settlement System; Magnetic Ink Character Recognition (MICR}; Electronic Funds Transfer (EFF}; Real Time Gross Settlement System (RTGS); Electronic Clearing Service (ECSJ